Program Belajar Islam Intensif bagi Muslimah di Desa Kenari, Kabupaten Pohuwato, Gorontalo - Asnawati Patuti; Riska; Eka Syahriani (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
Kenari Village is a village located in Lemito Subdistrict, Pohuwato Regency, Gorontalo Province. The people of Kenari Village have a religious character so that there are good enough da'wah opportunities for students of KKN STIBA Makassar in Gorontalo to develop the competence of da'wah in the field. The method of implementation of KKN is started by conducting field surveys using self-made instruments and then conducted SOAR analysis. After conducting observations and consultations with the Muslimah Wahdah Pahuwuto, then determined the kkn team work program as follows: Friday Study, Tahfiz Qur'an Daily, Adult Qur'an Education (Dirosa), Memorizing Hadith Kitabul Jami', Teaching Arabic, TPA / TPQ, Tahsin (improving reading). As a result, the KKN program can be carried out well and smoothly despite some changes and additions and time that are not as planned. As for the success achieved, it appears to improve the quality of reading the Qur'an muslimah and students in the location KKN.